Spiritual Poverty as a Cause of Corruption - Raden Nurhayati (al-Afkar, Journal For Islamic Studies, 2023)
Islam as we know is a religion that is always concerned with social interests, it can be seen from the pillars of faith and pillars of Islam. Social aspects that appear in the pillars of Islam shahada, prayer, zakat, fasting and pilgrimage. Of these five pillars, zakat is the pillar of Islam with the most obvious social aspect. By intending to give zakat, it means cleanliness, the cleanliness of our assets, some of which belong to other people, must be given to those who are entitled. In the midst of advising to pay zakat, on the other hand, many people commit acts of corruption, taking other people's rights. Corruption is strictly prohibited by Allah Swt and His Messenger and is an accursed act. Objectively, the government has been trying to realize good governance with deregulation and de-bureaucratization policies since 1980. A striking weakness in the process of achieving good governance so far is the high level of corruption accompanied by collusion and nepostism (KKN). If corruption is like this, then how to eradicate it? Efforts to eradicate corruption have been carried out both institutionally and individually, although many efforts have been made but the impact cannot be felt. All the negative effects caused by acts of corruption can be categorized as the biggest humanitarian violence in this country. Corruption is a social sin that destroys various structures of social life. In accordance with the word of Allah Swt in the Al-Qur'an verse al-Imran verse 112 which means "they are covered with humiliation wherever they are, unless they hold on to the rope (religion) of Allah and the rope (agreement) with humans. This paper aims to determine the impact and efforts to eradicate corruption in Indonesia. The writing method used is the method of literature review (library research). The impact caused by corruption in all lines of life has made Indonesia worse off because there are many corruption cases that have harmed the government and society, thus making Indonesia poorer. The most important efforts to eradicate corruption are moral movements and spiritual deepening which are continuously socialized from the basic level to the top level. The spiritual aspect is very important in human life, so when the spiritual aspect is lost in human life, humans do not get inner peace, there is no self-balance, especially when faced with increased material needs, they will become increasingly greedy because there is no more who can control himself.